Oh, the places you'll go! My many colored serotonin (apologies to Dr. Seuss) - Watts, Stephanie W (American journal of physiology. Heart and circulatory physiology, 2016)
Serotonin [5-hydroxytryptamine (5-HT)] has a truly fascinating history in the cardiovascular world. Discovered in the blood, 5-HT has long been appropriately regarded as a vasoconstrictor. A multitude of in vitro studies of isolated vessels support that addition of 5-HT causes vascular contraction. In only a few cases was 5-HT a vasodilator. Moreover, the potency and threshold of 5-HT causing contraction is increased in arteries from hypertensive vs. normotensive subjects, both animal and human. As such, we and others have hypothesized that 5-HT would contribute to hypertension by elevating arterial tone. In stark contrast to these decades of findings, we observed that a chronic infusion of 5-HT into conscious rats caused a reduction in blood pressure and nearly normalized blood pressure of experimentally hypertensive rats. Going back to the early work of Irvine Page, one of the scientists who discovered 5-HT, reveals an early recognized but never understood ability of 5-HT to reduce systemic blood pressure. Our laboratory, in collaboration with colleagues around the world, has dedicated itself to understanding the mechanisms of 5-HT-induced reduction in blood pressure. This manuscript takes you through a brief history of the discovery of 5-HT, in vitro serotonergic pharmacology of blood vessels, in vivo work with 5-HT and our studies that suggests the venous vasculature, potentially in combination with small arterioles, may be important to the actions of 5-HT in reducing blood pressure. 5-HT has certainly ended up in a place I never expected it to go.